2009
DOI: 10.1002/ddrr.78
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for fragile X syndrome: A closer look at the data

Abstract: Research into the determinants and developmental course of fragile X syndrome (FXS) has made remarkable progress over the last 25 years. However, treatments to ameliorate the symptoms of FXS have been less forthcoming. While there is optimism in the field that the pace of intervention research is quickening, there has been a bias toward psychopharmacological approaches to treatment. A closer look at the data from those investigations reveals a paucity of evidence that medications can improve intellectual and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 38 publications
(42 reference statements)
0
45
0
Order By: Relevance
“…The high prevalence of comorbid disorders in FRAX strongly indicates that treatment should be a primary concern of future research. At present, the first choice in the treatment of FRAX appears to be medication (Hall, 2009). Several studies have indicated that a large number of individuals with FRAX are prescribed psychotropic medications (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of comorbid disorders in FRAX strongly indicates that treatment should be a primary concern of future research. At present, the first choice in the treatment of FRAX appears to be medication (Hall, 2009). Several studies have indicated that a large number of individuals with FRAX are prescribed psychotropic medications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Berry- Kravis & Potanus, 2004;Valdovinos, Parsa, & Alexander, 2009). However, the evidence for the prescription of such treatments over other options has not been widely researched (Hall, 2009). Indeed few studies have evidenced the efficacy of other treatments such as behavioral interventions in the treatment of FRAX (Reiss & Hall, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between FMRP and behavioral/cognitive functioning may lead to the mistaken assumption that impairments in FXS can only be treated with medical or pharmacological interventions, such as mGluR5 antagonists or Lithium. In fact, Hall (2009) reviewed behavioral and pharmacological interventions for individuals with FXS and found a lack of evidence for the effectiveness of medications on the cognitive, adaptive, or behavioral functioning of individuals with FXS. Findings from a U.S. parent survey revealed that individuals with FXS do access other interventions such as speech-language therapy, occupational therapy, and, to a lesser extent, physical therapy and behavioral interventions .…”
Section: Biological and Environmental Influences On Behaviormentioning
confidence: 98%
“…These symptoms are generally treated with behavioral management and pharmacologically. Systematic review of pharmacological treatments finds a limited number of double blind control studies and raise questions about their efficacy [Hall, 2009;Rueda et al, 2009]. Thus, there is considerable interest in more specific and syndrome-based target treatments such as those based on the mGluR theory of FXS.…”
Section: Interventions: Behavioral Pharmacological and Neuromodulatorymentioning
confidence: 99%
“…It helps the family to recognize how the behavior is linked to the diagnosis; and, helps the clinician to make an appropriate referral for intervention by other experienced professionals and educators. As for treatment, behavioral management strategies and psychotropic medications are commonly used although there is need for more extensive study of their effectiveness [Hall, 2009]. When behavior therapies are utilized, an Moreover, in some instances, behavioral features in neurogenetic syndromes have been proposed as models for particular psychiatric disorders.…”
Section: Interventions: Behavioral Pharmacological and Neuromodulatorymentioning
confidence: 99%